The Relationship between Religiosity and Subjective Well-Being in Takmir Who Works as a Fisherman - Muhammad Khuzullifsar; M. K. P. Abdi Keraf; Dian Lestari Anakaka (Journal of Health and Behavioral Science, 2021)
This study aims to determine the relationship between religiosity and subjective well-being in Takmir mosque who works as a fisherman. The number of samples in this study was 40 fishermen in Kupang City who were Muslim. The data collection method was carried out using a questionnaire divided into three scales, namely the religiosity scale adapted from Satriani, (2011), and the two subjective well-being scales of the PANAS (Positive Affect and Negative Affect Scale) expressed by Watson, Clark, and Tellegen (1988) and SWLS (Satisfaction with Life Scale) based on the theory stated by Diener (1999). The results showed a significant relationship between religiosity and subjective well-being at the mosque takmir who works as fishermen where the Pearson Correlation value = 0.610 with a significance value of 0,000 (ƿ<0.05). This study aims to provide a new understanding of increasing welfare by increasing the religiosity value of the individual.